A smoothed particle hydrodynamics algorithm for multigrain dust with separate sets of particles. Issue 3 (15th October 2020) - Mentiplay, Daniel; Price, Daniel J; Pinte, Christophe; Laibe, Guillaume
ABSTRACT: We present a method for simulating the dynamics of a mixture of gas and multiple species of large Stokes number dust grains, typical of evolved protoplanetary discs and debris discs. The method improves upon earlier methods, in which only a single grain size could be represented, by capturing the differential backreaction of multiple dust species on the gas. This effect is greater for large dust-to-gas ratios that may be expected in the later stages of the protoplanetary disc life. We benchmark the method against analytic solutions for linear waves, drag, and shocks in dust–gas mixtures, and radial drift in a protoplanetary disc showing that the method is robust and accurate.